Introduction to sound : acoustics for the hearing and speech sciences - Speaks, Charles E. (Plural Publishing, 2018)
This textbook provides students in speech, language, and hearing science the thorough understanding of the elements of acoustics necessary to successfully embark on more advanced study of both normal and disordered human communication.